2022
DOI: 10.1111/ejn.15611
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and therapeutic role of Drp1 in the pathogenesis of Alzheimer's disease

Abstract: Alzheimer's disease (AD), a progressive neurodegenerative disorder, has emerged as the most common form of dementia in the elderly. Two major pathological hallmarks have been identified for AD: extracellular amyloid plaques and intracellular neurofibrillary tangles (NFT). Recently, dynaminrelated protein 1 (Drp1) was recognized to contribute significantly towards the pathogenesis of AD. Drp1 is primarily located in the cytosol, from where it translocates to the mitochondrial outer membrane and drives the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 201 publications
0
6
0
Order By: Relevance
“…In agreement, several groups have reported the potential of the pro-myelinating agent clemastine in reducing CNS amyloid pathologies and ameliorating cognitive deficits in AD mouse models [63][64][65]. Regarding the Drp1 hyperactivation provoking mitochondrial dysfunctions of OLs in AD [59], it is presumably not a cause but rather a consequence of amyloid-beta accumulation in these cells [66,67]. Zhang et al have shown that Drp1 is aberrantly hyperactivated in mature OLs cultured with cell-internalizable amyloidbeta [59,68].…”
Section: Exercise Counteracts Aging Brain Demyelinationmentioning
confidence: 70%
“…In agreement, several groups have reported the potential of the pro-myelinating agent clemastine in reducing CNS amyloid pathologies and ameliorating cognitive deficits in AD mouse models [63][64][65]. Regarding the Drp1 hyperactivation provoking mitochondrial dysfunctions of OLs in AD [59], it is presumably not a cause but rather a consequence of amyloid-beta accumulation in these cells [66,67]. Zhang et al have shown that Drp1 is aberrantly hyperactivated in mature OLs cultured with cell-internalizable amyloidbeta [59,68].…”
Section: Exercise Counteracts Aging Brain Demyelinationmentioning
confidence: 70%
“…From a clinical point of view, a SNP within the miR-1229 gene, which is expected to increase miR-1229-3p expression, was recently associated with increased risk for Alzheimer’s disease ( 45 ). Since both mitochondrial fragmentation and mitophagy deficiencies have been implicated in Alzheimer’s disease and several other neurodegenerative disorders ( 38, 46 ), investigating the role of the miR-1229-3p-Pink1 interaction in such disorders might be a promising direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies are focusing on Drp1 PTMs in fission. According to recent findings, Drp1 controls the dynamics of the fission process by moving from the cytosol to the OMM, where it interacts with other proteins that are part of the fission machinery, such as Fis1, Mff, Mid49, and Mid51 [ 27 , 28 ]. Table 1 presents critical information about the locations and molecular functions of major mitochondrial fission proteins.…”
Section: Mitochondrial Fissionmentioning
confidence: 99%